Budget imbalance as a consequence of distortions in withdrawals and subventions - Satanbekov, N.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article the author investigated the budgetary imbalance, the reason of which is in the existing distortions concerning withdrawal in the republican budget from donor regions and the subsequent subventions for regions recipients. The definition is given to the budgetary equalization and also the reasons which have an impact on the existing imbalance are stated. The comparative analysis of volumes of the budgetary withdrawals is carried out to the republican budget of four donor regions. Also the author carried out the analysis of the transferred volume of the budgetary subventions from the republican budget to regions recipients. The volumes of withdrawals and subventions are presented by years in the form of diagrams. In the article state programs of development of regions are mentioned, actions on prevention of the existing budgetary imbalance between regions are defined. In the research a conclusion is presented that nowadays the disproportion in formation of revenues of local budgets of certain regions is observed that serves as loading for the republican budget which in turn withdraws considerable financial resources from some regions and transfers to others. This problem is caused by regional differences in the plan of socio-economic development which such factors as population density, problems of uneven placement of productive forces and the fixed business assets, current state of the social sphere and also the level of development of a business sector on regions.
Шығарылымдар мен субвенциялардың бұрмалануының салдарынан бюджет теңгерімсіздігі
Бюджетный дисбаланс как следствие перекосов в изъятиях и субвенциях
Keywords: budget equalization; imbalance; transfers; withdrawals and subventions; donor regions; recipient regions